The Antitumor Peptide ERα17p Exerts Anti-Hyperalgesic and Anti-Inflammatory Actions Through GPER in Mice - Mallet, Christophe; Boudieu, Ludivine; Lamoine, Sylvain; Coudert, Catherine; Jacquot, Yves; Eschalier, Alain (Frontiers in Endocrinology, 2021)
Persistent inflammatory persistent pain, a major medical, social and economic burden related pharmacotherapy, needs to be continuously improved. The peptide ERα17p, which originates from a part of the hinge region/AF2 domain of the human estrogen receptor α (ERα), exerts anti-proliferative effects in breast cancer cells through a mechanism involving the hepta-transmembrane G protein-coupled estrogen receptor (GPER). It is able to decrease of the size of xenografted human breast tumors, in mice. As GPER has been reported to participate in pain and inflammation and hence we were interested in exploring the potential of ERα17p in this respect. We observed that the peptide promoted anti-hyperalgesic effects as from 2.5 mg/kg in a chronic mice model of paw inflammation induced by the pro-inflammatory complete Freund's adjuvant (CFA). This action was abrogated by the specific GPER antagonist G-15 leading to the conclusion that a GPER-dependent mechanism was involved. A systemic administration of a Cy5-labeled version of the peptide allowed its detection in both, the spinal cord and brain. However, ERα17p-induced anti-hyperalgesia was detected at the supraspinal level, exclusively. In the second part of the study, we have assessed the anti-inflammatory action of ERα17p in mice using a carrageenan-evoked hind-paw inflammation model. A systemic administration of ERα17p at a dose of 2.5 mg/kg was responsible for reduced paw swelling. Overall, our work strongly suggests that GPER inverse agonists, including ERα17p, could be used to control hyperalgesia and inflammation.